2021
DOI: 10.1186/s13058-021-01391-1
|View full text |Cite
|
Sign up to set email alerts
|

Leronlimab, a humanized monoclonal antibody to CCR5, blocks breast cancer cellular metastasis and enhances cell death induced by DNA damaging chemotherapy

Abstract: Background Triple-negative breast cancer (BCa) (TNBC) is a deadly form of human BCa with limited treatment options and poor prognosis. In our prior analysis of over 2200 breast cancer samples, the G protein-coupled receptor CCR5 was expressed in > 95% of TNBC samples. A humanized monoclonal antibody to CCR5 (leronlimab), used in the treatment of HIV-infected patients, has shown minimal side effects in large patient populations. Methods A humaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Treatment with maraviroc, CCR5 antagonist, significantly suppresses bone metastasis in a xenograft rat model implanted with breast cancer cells (MDA-MB-231) (131). Leronlimab (PRO 140) is another CCR5 antagonist under investigation in breast cancer clinical trials (129,132,133).…”
Section: The Ccr Familymentioning
confidence: 99%
“…Treatment with maraviroc, CCR5 antagonist, significantly suppresses bone metastasis in a xenograft rat model implanted with breast cancer cells (MDA-MB-231) (131). Leronlimab (PRO 140) is another CCR5 antagonist under investigation in breast cancer clinical trials (129,132,133).…”
Section: The Ccr Familymentioning
confidence: 99%
“…Transwell migration assay was performed in 24 well transwell inserts (Corning, Tewksbury, MA, USA) as previously described [ 103 , 104 ]. See the supplemental methods for the details.…”
Section: Methodsmentioning
confidence: 99%
“…CCR5 is overexpressed breast [ 84 , 94 ], prostate [ 92 ], pancreatic, colorectal [ 95 , 96 ], head and neck [ 97 ], gastric [ 87 ], and esophageal [ 98 ] cancer as well as acute lymphocytic leukemia [ 99 ], melanoma, Hodgkin’s lymphoma, and other tumors [ 88 , 93 ]. In humans, CCR5 has the peculiar characteristic of being a developmentally nonessential gene, which participates in diverse pathological processes, including infection with HIV [ 100 , 101 , 102 , 103 ], progression of stroke [ 104 ], and cancer metastasis [ 84 , 93 , 105 ]. Although metastasis involves multiple distinct steps, CCR5 was shown essential to govern the homing step of breast cancer metastasis in mice, as demonstrated by the anti-metastatic activity of the CCR5 inhibitor maraviroc [ 84 , 93 , 105 ].…”
Section: Cellular Cross Talks By Chemokines and Their Receptorsmentioning
confidence: 99%
“…In humans, CCR5 has the peculiar characteristic of being a developmentally nonessential gene, which participates in diverse pathological processes, including infection with HIV [ 100 , 101 , 102 , 103 ], progression of stroke [ 104 ], and cancer metastasis [ 84 , 93 , 105 ]. Although metastasis involves multiple distinct steps, CCR5 was shown essential to govern the homing step of breast cancer metastasis in mice, as demonstrated by the anti-metastatic activity of the CCR5 inhibitor maraviroc [ 84 , 93 , 105 ]. Subsequent studies showed the importance of CCR5 in both the formation of new metastasis and the growth of previously formed breast [ 105 ] and gastric cancers [ 106 ].…”
Section: Cellular Cross Talks By Chemokines and Their Receptorsmentioning
confidence: 99%
See 1 more Smart Citation